PENERAPAN KONSEP DAN TEORI KEPERAWATAN PADA IBU HAMIL DENGAN PLASENTA PREVIA - Astari, Asti Melani (University of Muhammadiyah Malang, 2012)
Placenta previa is one of situations that lead to bleeding during pregnency. Pregnency mother with Placenta previa have to be handled by medical worker/staff as soon as possible to keep mother and her embryo safely. Nurse as one of medical staffs giving nurse guidence comprehensively play important role in monitoring mother and her fetus continualy. The nurse prepares mother to face giving birth and taking care her fetus condition. The objective of this report was to figure out conceptual and theoritical application of nurse in nurse guidance on antepertum mother with Placenta previa and nurse role as a guide, concelor, advocate, educator, coordinator, colaborator, communicator, alteration agent and researcher in directing of antepertum mother with Placenta previa. Choosing conceptual and theoritical nurse was based on clien contact having ability on adaptation, humanisticaly and having complicated- condition that lead to existancy of anxiety. Therefore it was precisely used Adaptation Concept and Theory from Roy, Need for Help from Wiedenbach, Interpersonal Relation from Peplau, Human Caring of Watson and Family Centered-Maternity Care Concept in giving nurse guidance on pregnant mother with Placenta previa. It was expected that pregnant mother with Placenta previa keep in her optimal condition, can adapt physically and phycologically, and is ready to face giving birth process.